Metamaterial boat fenders with supreme shape recovery and energy absorption/dissipation via FFF 4D printing - Bodaghi, Mahdi; Namvar, Naser; Yousefi, Armin; Teymouri, Hadi; Demoly, Frédéric; Zolfagharian, Ali (Smart materials and structures, 2023)
In maritime transportation, a fender acts like a bumper to absorb the kinetic energy of a boat berthing against a jetty, pier wall, or other boats. They have high energy absorption and low reaction forces, preventing damage to boats and berthing structures. The aim of this paper is to introduce a novel conceptual design for a new class of lightweight boat-fendering systems with superior energy absorption/dissipation and shape recovery features. Different metamaterials with honeycomb, re-entrant, and re-entrant chiral auxetic patterns are designed in the form of boat fender panels, and their thermo-mechanical behaviors are analyzed experimentally and numerically. A finite element modeling (FEM) is developed to investigate the compressive behaviors of boat fenders. Some of designs are 4D printed by fused filament fabrication of shape memory polylactic acid polymers and then tested thermo-mechanically. A good correlation is observed between numerical and experimental results, supporting the FEM accuracy. Results reveal that proposed boat fenders have considerable energy absorption/dissipation along with the capability to fully recover plastic deformations by simply heating up. The excellent mechanical property recovery of the proposed boat-fendering system is also shown under cycling loadings. Due to the absence of similar conceptual designs, models, and results in the specialized literature, this paper is expected to be instrumental towards 4D printing novel boat fenders with supreme energy absorption/dissipation and shape recovery properties promoting sustainability.